Injectable Interpenetrating Network Hydrogels for Biomedical Applications - Gilbert, Trevor (My University, 2017)
Interpenetrating polymer networks (IPN’s) consist of two overlapping cross-linked networks that are not bonded to each other. Hydrogel IPN’s are of application interest due to properties such as mechanical reinforcement, modulated drug release and biodegradation kinetics, dual polymer activities in vivo, and novel nanostructured morphologies. Prior IPN hydrogels reported in the literature either required surgical implantation (disadvantageous for several reasons) or were polymerized in situ (limited to a small subset of biologically safe chemistries). Alternatively, we formed IPN’s using a mixing injector to deliver orthogonally reactive functionalized prepolymer solutions that gel upon contact. Specifically, we use hydrazone chemistry to gel a thermosensitive poly(N-isopropylacrylamide) (PNIPAM) network and kinetically orthogonal thiosuccinimide or disulfide chemistry to cross-link a second network of hydrophilic poly(vinylpyrrolidone) (PVP). The resulting IPN’s preserve the thermoresponsive properties of the PNIPAM constituent but exhibit slower, smaller, and more reversible transitions due to entanglement with the highly hydrophilic PVP network (potentially useful to reduce the problem of burst release in thermoresponsive drug delivery systems). Mechanical reinforcement was evidenced by the increased shear storage modulus of IPN composites relative to the sum of the individual component moduli, particularly so in IPN’s employing the thiosuccinimide-cross-linked PVP. The nanostructure of the IPN hydrogels was further studied using small angle neutron scattering with contrast matching, and was found to combine features characteristic to each single network component (PNIPAM-rich static domains embedded in PVP-rich fractal clusters). However, our results suggest some slight changes to their scattering profiles, indicative of partial mixing or influence of each network structure upon the other. Corroborating investigations with single-molecule super-resolution fluorescence microscopy, operating at a slightly larger length scale, show the formation of separate populations of mixed and individual domains or clusters of each polymer type. These properties suggest such injectable IPN’s for further investigation as prospective biomaterials.
Keywords: Hydrogel; Interpenetrating network; PolyNIPAM; PVP; Injectable; Biomaterials